ANALISIS TANTANGAN DAN SOLUSI DALAM MENGINTEGRASIKAN TRI HITA KARANA KE DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR SD NEGERI 2 BATUR: ANALISIS TANTANGAN DAN SOLUSI DALAM MENGINTEGRASIKAN TRI HITA KARANA KE DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR SD NEGERI 2 BATUR - Mahendra, Ngakan Ersa; Sudirman, I Nyoman (ITP Marakandeya Bali, 2025)
This study aims to analyze the challenges and solutions in integrating Tri Hita Karana into science learning (IPAS) at Sekolah Dasar Negeri (Public Elementary School) 2 Batur. Tri Hita Karana is a principle of life that emphasizes the balance between devotion to God, service to fellow humans, and fostering love for the environment and living beings around us. The results of this study indicate that students at SD Negeri 2 Batur have diverse backgrounds and understandings of spiritual and social values. The solution to overcome these challenges is to provide adequate training for teachers on how to integrate Tri Hita Karana into science learning (IPAS).